The Effect of Educational Intervention Based on Theory of Planned Behavior Approach on Complementary Feeding: A Randomized Controlled Trial - Qonita Rachmah; Junaida Astina; Dominikus Raditya Atmaka; Leli Khairani (International Journal of Pediatrics)
Complementary feeding should be given to infants at 6 months in addition to breastmilk. Mothers’ knowledge and behavior in giving adequate complementary feeding are crucial to prevent malnutrition risk. During the pandemic, conventional nutrition education cannot be maintained and could lead to decreased mothers’ knowledge. This study is aimed at analyzing the effectiveness of nutrition education using online digital platforms (WhatsApp) to improve a mother’s behavior in providing nutritious complementary food based on the theory of planned behavior approach. This was a quasiexperiment with one pretest and posttest design group in the form of education and counselling. Ten educational sessions were developed to improve one or more TPB constructs. Media used for education are PowerPoint, text description, posters, and video tutorials; it is implemented by sending materials through the WhatsApp application. Using 80% power, the sample size was calculated for 155 subjects. Subjects were recruited through the accidental sampling method. Data was collected by the online method using a validated open-ended self-developed questionnaire for knowledge, while attitude, subjective norms, intention, and self-efficacy were measured using a Likert-scale questionnaire, where participants rated the strength of their belief that they could engage in a specific task. The paired t-test was used to analyze the difference in outcomes measured. The response rate of this study was accounted for at 77.5%. The mean age of mothers was 28.2 years old; most of them were university graduates (80.2%) and working as private sector workers (40.0%). The average child’s age was 6.6 months old. 78.2% of children were exclusively breastfed. Our study revealed that 10 sessions of nutrition education and counselling covered over 8 days increased the mother’s knowledge (60.0±15.5 vs. 80.3±15.0, respectively, before and after education; p<0.005) and resulted in psychological changes including mother’s attitude (64.3±4.9 vs. 65.8±3.9), subjective norm (3.76±0.9 vs. 3.87±1.0), perceived behavioral control (3.78±0.9 vs. 4.12±0.12), self-efficacy (63.3±22.5 vs. 77.5±19.2), and intention toward giving nutritious complementary feeding (4.11±1.0 vs. 4.30±0.9; p<0.005). WhatsApp nutrition education proved to be effective in improving the mother’s knowledge and behavior in providing nutritious complementary food; thus, it has potential for use. In the future, the Ministry of Health from the district to the national level could implement this type of education as an alternative of conventional nutrition education through scheduled classes.